The water quality monitoring of vannamei shrimp (Litopenaeus vannamei) ponds in East Tanete Riattang District, Bone Regency, Indonesia - Harlina Harlina; Ilmiah Ilmiah; Andi Hamdillah; Dewi Virgiastuti Jarir; Ahmad Darul Salam (Depik, 2022)
The monitoring of water quality is an essential process of shrimp production. This study aimed to evaluate the water quality based on physical, chemical, and biological parameters in a vannamei shrimp pond, which is managed by an intensive system in East Tanete Riattang District, Bone Regency. The sampling of parameters was conducted from March to April 2020 at the ponds in three villages, which include Waetuo (station A), Panyula (station B), and Toro (station C). The water quality was evaluated at each sampling site based on certain factors, such as dissolved oxygen (DO), temperature, salinity, pH, ammonia, and bacterial population. The results showed that the temperature, salinity, pH, DO, and bacterial populations ranged from 26 to 30 C, 25 to 35 ppt, 5.5 to 7.0, 5.5 to 7.0 ppm, and 3.5 101 to 2.1 103, respectively. According to the National Standard of Indonesia for shrimp culture, the range of these water quality parameters was suitable for vannamei shrimp life. Meanwhile, the level of ammonia was 1.7 to 1.8 ppm, which exceeded the normal range that supports the vannamei shrimp life-cycle.Keywords:Water quality, Ponds, Litopenaeus vannamei,Ammonia,Vibriosis